PENGARUH RIGHT ISSUE TERHADAP LIKUIDITAS SAHAM - Ratnaningrum Ratnaningrum (JURNAL LITBANG PROVINSI JAWA TENGAH, 2008)
The aim of this research was to obtain empirical evidence about the influence of the right issue to the decision to be taken by investor . The choosen sample is the company that have brought outside the right issue in 2002 - 2004. This study use measurement with trading volume activity (TVA) and bid ask spread. To prove differentiation of trading volume activity and relative spread before and after the announcement of right issue, this study has used two paired sample test. The results of this research are indicated that the right issue has no information enough to investors’ preference. Researcher has judged that other factors that can influence to trading volume and bid ask spread, like the ownership cost and asymetri information are necessary to be control to get the different result.